Social-emotional learning is essential to classroom management. (October 2014) - Jones, Stephanie M.; Bailey, Rebecca; Jacob, Robin
Research tells us that children's social-emotional development can propel learning. A new program, SECURe, embeds that research into classroom management strategies that improve teaching and learning. Across all classrooms and grade levels, four principles of effective management are constant: Effective classroom management is based in planning and preparation; is an extension of the quality of relationships in the room; is embedded in the school environment; and includes ongoing processes of observation and documentation.